Downward accountability in response to collective actions1. Issue 1 (January 2014) - Li, Yuan
Abstract Will autocratic governments implement policies to satisfy the people's demands in order to prevent large scale social unrest? This article explores this question through quantitative analysis of the political economy of public goods provision in Chinese provinces. Data were collected on the number of labour disputes to measure collective actions. My sample includes provincial leaders whose incentives to deliver public goods can either be explained as a result of upward accountability towards the Centre or downward accountability towards the citizens. The confounding factor of upward accountability is ruled out by using two‐step estimation, and the reverse causality between public goods provision and collective actions is controlled by using instrumental variables. This result suggests that provincial leaders will implement policies more in favour of the citizens in response to intensified labour disputes.